Crowdsourced Identification of Potential Target Genes for CTV Induced Gene Silencing for Controlling the Citrus Greening Vector Diaphorina citri - Ramos, John E.; Jain, Ritesh G.; Powell, Charles A.; Dawson, William O.; Gowda, Siddarame; Borovsky, Dov; Shatters, Robert G. (Frontiers in Physiology, 2021)
Citrus Greening or Huanglongbing (HLB) is a disease of citrus, causing high reduction in citrus production and is transmitted by the Asian citrus psyllid Diaphorina citri Kuwayama vectoring a phloem-limited bacterium Candidatus Liberibacter sp. We report research results using crowdsourcing challenge strategy to identify potential gene targets in D. citri to control the insect using RNA interference (RNAi). From 63 submitted sequences, 43 were selected and tested by feeding them to D. citri using artificial diet assays. Following feeding on artificial diet The 3 most effective dsRNAs exhibited 30% mortality above control targeted genes expressing; iron-sulfur cluster subunit of the mitochondrial electron transport chain complex (Rieske), heme iron-binding terminal oxidase enzyme (Cytochrome P450) and tetrahydrobiopterin (BH4) pathway enzyme (Pterin 4α-Carbenolamine Dehydratase). The dsRNA sequences were cloned into a citrus phloem-limited virus (citrus tristeza virus, CTV T36) expressing dsRNA against these target genes. The use of this viral mediated “para-transgenic” citrus plant system caused higher adult D. citri mortality than what was observed using artificial diet, reaching 100% when detached citrus leaves with the engineered CTV expressing dsRNA were fed to adult D. citri. Using this approach, a virus-induced gene silencing (VIGS) can be used to test future transgenic cultivars before genetically engineering citrus. RNA Seq analysis using next-generation sequencing identified genes upstream and downstream of the targeted genes that were transcriptionally modified. These genes were annotated showing that many are associated with the primary function of the Rieske (electron transport chain) gene that was targeted by VIGS.